Building the posterior lateral line system in zebrafish - Chitnis, Ajay B (2012)
The posterior lateral line in zebrafish has emerged as an excellent system to study how a sensory organ system develops. Here we review recent studies that illustrate how interactions between multiple signaling pathways coordinate cell fate, morphogenesis and collective migration of cells in the posterior lateral line primordium. These studies also illustrate how the posterior lateral line system is contributing much more broadly to our understanding of mechanisms operating during the growth, regeneration and self-organization of other organ systems during development and disease.